The role of women in South Kurdistan in writing memoirs (1999 - 2003) - Bapir, Asst.L. Shuan Ahmad (Sulaimani Journal for Humanities, 2026)
Memoirs are considered to be one of the most common ways of writing individuals' life experiences today. Individuals express their personal lives for several purposes and also hang a picture of their past in their narratives It is a specific goal of the writers' memoirs. This study attempts to show the role of women in South Kurdistan in writing memoirs, to what extent they have been able to show their place alongside men in this field and pass on their past experiences to the generations of this era. The research method of this research is analytical method, during the collection of data and analysis to fill the gaps and find out the factors that affected women memoir writers. The scope of this research is between 1999-2003 They have not tried to base their writings on historical documents. A small number of southern Kurdish women have realized writing their life experiences during this period, which is linked to several obstacles including: political, economic, social, feelings of a kind Women are marginalized in this area.
Keywords: Memoirs; Nahidah Sheikh Salam; Bahya Maroof Barzanji; Pakiza Rafiq Hilmi